The (ir)resistable job offer - Kulakarṇī, Vaishṇavī (London : Indian Institute of Management, Ahmedabad, 2018)
The case revolves around a job offer received by Vinita Upadhyay, a journalist working with a regional daily, Divya Bhaskar, in Ahmedabad, Gujarat. Taking up the offer would mean a shift from journalism and require Upadhyay to join the public relations industry. The case provides three different perspectives regarding this offer. It begins with Upadhyay's perspective, followed by the views of Geet Sethi, who offered her the job, and finally, that of Minesh Modi, who is her maternal uncle. The case indicates that Upadhyay is not keen on taking up the offer, partly because of her own biases and beliefs regarding the job and role expectations. Modi, however, is convinced that this is an excellent opportunity for Upadhyay and is determined to persuade her to make the shift.
Originally Published In Kulkarni, V. (2018). The (Ir)resistible Job Offer. COMM0019. Ahmedabad, India: Indian Institute of Management, Ahmedabad.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Upadhyay, Vinita; Sethi, Geet; Modi, Minesh; Divya bhāskara; Career changes -- India -- Gujarat -- Case studies; Job offers -- India -- Gujarat -- Case studies